Construction of Lattice Strain in Bimetallic Nanostructures and Its Effectiveness in Electrochemical Applications. Issue 46 (7th August 2021) - Li, Can; Yan, Shaohui; Fang, Jiye
Abstract: Bimetallic nanocrystals (NCs), associated with various surface functions such as ligand effect, ensemble effect, and strain effect, exhibit superior electrocatalytic properties. The stress‐induced surface strain effect can alter binding strength between the surface active sites and reactants as well as their intermediates, and the electrochemical performance of bimetallic NCs can be significantly facilitated by the lattice‐strain modification via their morphologies, sizes, shell‐thickness, surface defectiveness as well as compositions. In this review, an overview of fundamental principles, characterization techniques, and quantitative determination of the surface lattice strain is provided. Various strategies and synthesis efforts on creating lattice‐strain‐engineered bimetallic NCs, including the de‐alloying process, atomic layer‐by‐layer deposition, thermal treatment evolution, one‐pot synthesis, and other efforts are also discussed. It is further outlined how the lattice strain effect promotes electrochemical catalysis through the selected case studies. The reactions on oxygen reduction reaction, small molecular oxidation, water splitting reaction, and electrochemical carbon dioxide reduction reactions are focused. In particular, studies of lattice strain arisen from core–shell nanostructure and defectiveness are highlighted. Lastly, the potential challenges are summarized and the prospects of lattice‐strain‐based engineering on bimetallic nanocatalysts with suggestion and guidance of the future electrocatalyst design are envisioned. Abstract : After an outline of fundamental principles, synthesis strategies to create lattice strain in bimetallic nanocrystals are discussed. The following case study further demonstrates how the lattice strain promotes electrochemical catalysis in oxygen reduction reaction, small molecular oxidation, water splitting, and electrochemical CO2 reduction reaction. Potential challenges and prospects in this realm are also summarized and proposed.